Modelling pedestrians’ utilisation of crossing facilities, gap acceptance and crossing decision in urban area - Ali Al Bargi, Walid Abdullah (2018)
A pedestrian intending to cross a roadway has to decide whether to use a crossing facility or to cross a street illegally. An incorrect decision made will expose the pedestrian to the risk of accident. Pedestrian crossing behaviour has been sighted in the focus in the last decades. In the past, several studies investigating the risk of crossing a road focusing on walk trip frequency or mode choice behaviours have been conducted. Numerous factors which affect the behaviour of pedestrians have been identified. Up to now, far too little attention has been paid to pedestrian road crossing behaviour in Malaysia. The specific aim of this study was to provide new insights and develop models for pedestrian gap acceptance, crossing decision and utilisation of zebra crossings among pedestrians using regression model techniques. The critical gaps for pedestrians were estimated using Raff’s method from studies conducted at 12 locations in different regions across Malaysia. The results show that the average critical gap was 9.9 seconds. Studies on gap acceptance found that nine factors such as baggage effect, pedestrian gender, vehicle size, crossing distance and etc influenced the pedestrians’ crossing behaviour in terms of accepted gap size. Meanwhile, studies on crossing decision showed that four parameters, i.e. traffic speed, driver yield, pedestrian number and pedestrian age significantly influenced pedestrians’ crossing choice. In addition, the findings indicated that while there were three significant factors i.e. length of zebra crossing, guardrail and number of lanes that positively influenced the pedestrian utilisation rate of crossing facilities, four variables were found to have significant direct effect on the decision to use zebra crossings. The models developed for pedestrians’ use of zebra crossings, gap acceptance and crossing decision were found to be significant and thus can be used to gauge the pedestrians’ crossing behaviour in urban areas. Hence, this study would help improve pedestrian crossing behaviours and influence the local authorities to draw up street design policies and pedestrian facility specifications that will improve the safety of pedestrians and other road users in Malaysia.